Building and using flexible models incorporating grey-level information - Cootes, Timothy F.; Taylor, Chris J.; Lanitis, Andreas; Cooper, D.H.; Graham, J. (My University, 1993)
This paper describes a technique for building compact models of the shape and appearance of flexible objects seen in 2-D images. The models are derived from the statistics of sets of labelled images of example objects. Each model consists of a flexible shape template, describing how important points of the object can vary, and a statistical model of the expected grey levels in regions around each model point. Such models have proved useful in a wide variety of applications. We describe how the models can be used in local image search and give examples of their application.
Keywords: Flexible objects models; Flexible models; Grey-level information; Compact models; 2-D images; Labeled images; Flexible shape template; Statistical model; Local image search